Magnetic Levitation for Diamagnetic Material Density Measurement: Theoretical Studies - Gancang Saroja (Natural B, Journal of Health and Environmental Sciences, 2014)
A theoretical study was conducted to measure the density of diamagnetic materials using magnetic levitation method. In this study, cylindrical permanent magnet was used for generating a magnetic field gradient and a paramagnetic fluid as media of levitation. Both methods which using a single and double source were studied. The measureable parameter was the high of material levitation. The results showed that both methods can be used to measure the density of the diamagnetic sample.